Waves - Quebec Writers' Federation (QWF) (2018)

Van-Seasons - Quebec Writers' Federation (QWF) (2019)

The Tourist Offer of the Whiteley Museum and its Surrounding Area on the Lower North Shore : A Quality Improvement Report - Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2022)
This report analyzes the tourist offer in the eastern part of Quebec’s Lower North Shore, particularly the municipality of Bonne-Espérance, a region where English speakers make up the majority of the population. It focuses specifically on an institution in one of these municipalities, the Whiteley Museum. The report provides the authors’ suggestions to improve tourism development as a means to diversify the economy, potentially help reverse demographic decline, and build community vitality.

Response to CAM Report on Systemic Racism in the Arts - English Language Arts Network (ELAN) (2019)

Project Report : Community Health and Social Services Network (CHSSN) : Community Radio : January 1 to March 31, 2007 - Howarth, Kelly; Kueber, Russell (Community Health and Social Services Network (CHSSN), 2007)
The findings and processes were to be documented and shared with the Lower North Shore (local radio station and regional English-speaking organization, COASTERs Association). In addition, consultation and support was to be given to both service providers to increase their capacity to better serve the English-speaking regions in the future.

Musée Ambulant visits the Lower North Shore! - English Language Arts Network (ELAN) (2020)

Haiku Counting Book - Quebec Writers' Federation (QWF) (2018)